Experimental and Theoretical Investigation of the First‐Order Hyperpolarizability of Octupolar Merocyanine Dyes. Issue 12 (20th June 2014) - Castet, Frédéric; Blanchard‐Desce, Mireille; Adamietz, Frédéric; Poronik, Yevgen M.; Gryko, Daniel T.; Rodriguez, Vincent
Abstract Hyper‐Rayleigh scattering experiments and quantum chemical calculations are combined to investigate the second‐order nonlinear optical responses of a series of three‐arm merocyanine derivatives. They exhibit an octupolar hyperpolarizability response with lower amplitude than crystal violet due to a lower extent of the photoinduced charge transfer and reduced bond length alternation. Strong effects on the second‐order optical response measured close to the two‐photon absorption level are clearly evidenced; for example, the effective measured polarization ratio deviates below the ideal octupolar value of 3/2 even at very low excitation power. These effects are attributed to two‐photon absorption resonance, which we believe modifies dynamically the population of the ground state versus that of the excited state.